Izučenie gazetno-publicističeskogo stilâ v SSSR (Rossii) v 50-90-e gg. XX v. - Solganik, Grigorij Â. (Stylistyka, 2021)
The author sums up the achievements of Russian stylistics in the field of investigating the language of the press in the second half of the 20th century.